Inhibition of bromodomain and extra-terminal proteins (BET) as a potential therapeutic approach in haematological malignancies: emerging preclinical and clinical evidence. (June 2015) - Chaidos, Aristeidis; Caputo, Valentina; Karadimitris, Anastasios
Post-translational modifications of the nucleosomal histone proteins orchestrate chromatin organization and gene expression in normal and cancer cells. Among them, the acetylation of N-terminal histone tails represents the fundamental epigenetic mark of open structure chromatin and active gene transcription. The bromodomain and extra-terminal (BET) proteins are epigenetic readers which utilize tandem bromodomains (BRD) modules to recognize and dock themselves on the acetylated lysine tails. The BET proteins act as scaffolds for the recruitment of transcription factors and chromatin organizers required in transcription initiation and elongation. The recent discovery of small molecules capable of blocking their lysine-binding pocket is the first paradigm of successful pharmacological inhibition of epigenetic readers. JQ1 is a prototype benzodiazepine molecule and a specific BET inhibitor with antineoplastic activity both in solid tumours and haematological malignancies. The quinolone I-BET151 and the suitable for clinical development I-BET762 benzodiazepine were introduced in parallel with JQ1 and have also shown potent antitumour activity in preclinical studies. I-BET762 is currently being tested in early phase clinical trials, along with a rapidly growing list of other BET inhibitors. Unlike older epigenetic therapies, the study of BET inhibitors has offered substantial, context-specific, mechanistic insights of their antitumour activity, which will facilitate optimal therapeutic targeting in future. Here, we review the development of this novel class of epigenetic drugs, the biology of BET protein inhibition, the emerging evidence from preclinical work and early phase clinical studies and we discuss their potential role in the treatment of haematological malignancies.